Attention Deficit Hyperactivity Disorder (ADHD) and Offending Behaviour- Case Report - Olubokun, Jibowu (International Journal of Criminology and Sociology, 2014)
The association between Attention Deficit Hyperactivity Disorder (ADHD) and Offending behaviour is well documented in Literature. The DSM IV and the NICE Clinical guidelines state that Hyperactivity, Impulsiveness and poor concentration are the core features of this condition. Attention Deficit Hyperactivity Disorder can be seen as a Neurodevelopmental disorder and a spectrum disorder. In this case report the discontinuation of pharmacological treatment with Modified release preparation of Methyl phenidate Hydrochloride led to an escalation of offending behaviour within a few weeks which resulted in an admission into a Secure Children’s facility in Leeds West Yorkshire and Subsequent ‘Electronic tagging’ in a 15 year old. Some young persons with ADHD can present with ‘complex needs’ and Health care professionals, Drug workers and other staff as well as Forensic Physicians working within the Custodial and Forensic settings would need to be sensitive and responsive to their needs in order to ensure the continuity of treatment for as long as is practicable and achievable even whilst in custody. The importance of multidisciplinary and multiagency working with a ‘joined up’ approach so as to maximise out come is highlighted.